Maternal and perinatal outcomes in pregnancy with high BMI in the Jabal Akhdar region of Libya - Elghazal, Zahia; Langhe, Ream; Bettamer, Nagat; Hamad, Karima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Overweight maternal pre-pregnancy, obesity and excessive gestational weight gain are significant risk factors for unfavorable maternal and perinatal outcomes during pregnancy. The association of obesity with maternal and perinatal outcomes is poorly understood in Jabal Akhdar region of Libya. This study was to examine maternal and perinatal outcomes in obese mothers compared to non-obese mothers in Jabal Akhdar region of Libya. Methods: This is a Cross sectional survey design study with internal comparison groups. The study was conducted between May 2015 and May 2016 in Jabal Akhdar region od Libya. A total of 415 women at reproductive age were deemed eligible for this study. BMI categories were defined as; underweight (BMI< 18.5), normal (BMI 18.5 – 24.99), overweight (BMI 25 – 29.99), grade I obesity (BMI 30 – 34.99), grade II obesity (BMI 35 – 39.99) and grade III obesity (BMI 40+). Data obtained in this study was analysed using SPSS, version 17.0 was used in analysis. Results: Of 415 women included in this study, 282 had a BMI <30 kg/m2 and 133 women had a BMI >30 kg/m2. Pregnancy-induced hypertension was more prevalent in obese mothers compared to non-obese women. The rate of operative delivery and caesarean section were also demonstrated between obese and non-obese mothers and these differences were significant. Conclusions: This study demonstrates extent of obstetric risks associated with obesity in pregnancy, though more research is required to fully elucidate the effect that maternal obesity is having on maternal and perinatal outcomes in pregnancy in Libyan populations. Since high weight gain is a modifiable risk factor, pre pregnancy health education awareness of health care providers, good behavioral counseling and weight control program during pregnancy should help to modify this risk.